Parameters of Dental X-Ray Exposure in Dental Patient Absorbed Dosage Calculation - Ain, S.T., M.Si., Dr. Khusnul; Masykuriyah, Dewi; Rahayuingsih, Betty (Universitas Airlangga, 2022)
A dental x-ray is an x-ray used for checking teeth. During the inspection process, the patient will receive the dose resulting from the function of the formation of x-rays. To know the magnitude of the dose, the radiation measurement tool required, and any instances of the hospital do not have it. To see the magnitude of the dose, a radiation measurement tool was needed. In many cases, the hospital did not have it, so the hospital had to borrow instruments to measure the radiation. With these problems, the purpose of this research is to know the value exposed parameters and can calculate the weight of the absorbed dose without the use of tools to measure the radiation. Using the equation of exposure then, it can calculate exposed parameters and then know the absorbed dose received by the patients teeth. This research was conducted with fifteen tools and dental x-rays with various merk and types. The fifteen tools will have a value of expose parameters that is different because it depends on the voltage waveform, the filtration, and the beam size used. This research is done by placing the proper dose measurement tools under the CONUS cylinder. The radiation measurement tool will connect to the computer with ocean applications that read the dose number. In the process expose, wich in the set is expose time. The greater the time hence, the larger the dose also accepted. And obtained a value of expose parameters minimum of 2,109, while the value tells parameters maximum of 21,937.